GEOLOGY AND PETROGRAPHY OF ILUKE, NORTH CENTRAL BASEMENT COMPLEX, KIRI SHEET 226, (SW OF NIGERIA) - Alfa, M. P.; Danbatta, U. A.; Jolly, B. A.; Mahmud, I. (FUDMA Journal of Sciences, 2024)
A systematic geological mapping of Iluke, Kiri sheet 226 SW, (Nigeria) was carried out on a scale of 1:50,000.The study shows Migmatite-gneiss complex, Schist, Quartzite and the granitoids, as the major rocks, the minor rocks observed are the amphibolite, pegmatite dykes and veins, while the superficial deposits mapped include laterite and alluvial sands. The schist and amphibolite were subjected to thin section where the petrography of Schist and amphibolite was carried out under Plane Polarized Light (PPL) and Cross Polarized Light (XPL) which revealed mineral assemblages which correspond to the metamorphic facies of the upper greeenschist (Quartz, Chlorite, Sericite, muscovite and plagioclase) and the lower amphibolite facies (Hornblende or amphibole, plagioclase, Quartz, Biotite) that indicates a regional metamorphism. An ultramylonites with less than 10% porhyroblast was observed in the studied area which indicates a dislocation metamorphism. These was done to understand the occurrence of rocks and to determine the metamorphic grade of the study area.